Equity research in the automotive industry: valuation of BMW: BMW’s success at crossroads - Olschewski, Marcel Philipp (2020)
This work project “Equity Research –Valuation of BMW” analyzes BMW’s business within the automotive industry. Given as trong demand for BMW’s luxury cars, e.g. SUVs, we estimate further modest sales growth of 1.2%-1.6%in a challenging environment. However, this imposes potential fines for missing EU CO2fleet emission target but also finance the necessary R&D and CAPEX needs to master the current sector trends. This results in a lower operating profitability in the future. Our valuation for BMW yields a price target of €75.52for FY20, which results in a 7.4% total shareholder return and hence, a HOLD recommendation